Kualitas Bahan Bakar Biogas Limbah Cair Tahu Dengan Penggunaan Variasi Komposisi Starter - Nely Ana Mufarida; Asroful Abidin (Universitas Muhammadiyah Sidoarjo, 2020)
Fossil fuels are a primary energy source. Fossil fuels that are widely used are in the form of fuel oil, gas fuel, and coal. Along with technological developments, the need for fossil fuels is increasing, which is followed by the depletion of supplies. Therefore, renewable energy is needed which is cheap and easy to use on a household scale such as biogas. Therefore, renewable energy is needed, which is cheap and easy to use on a household scale such as biogas. The materials used as biogas are tofu liquid waste with a yeast starter, EM-4, and horse manure. Tests on the quality of tofu liquid waste biogas conducted in this study include; Gas volume, temperature, degree of acidity (pH), C/N ratio, and gas content, namely methane (CH4), hydrogen sulfide (H2S), carbon monoxide (CO), and oxygen (O2). In the test results, it was found that the increase in the quality of tofu liquid waste biogas by using horse dung starter was producing a volume of 513.6 ml, a temperature of 31.7oC, a C/N ratio of 5.336, a CH4 content of 69%, and H2S content of 5 ppm, a CO content of 9 ppm and an O2 content of 16.3%.